Modelling the chemistry and transport of bromoform within a sea breeze driven convective system during the SHIVA Campaign - Lim, P.T. (Atmospheric Chemistry and Physics, 2013)
We carry out a case study of the transport and chemistry of bromoform and its product gases (PGs) in a sea breeze driven convective episode on 19 November 2011 along the North West coast of Borneo during the “Stratospheric ozone: Halogen Im- 5 pacts in a Varying Atmosphere” (SHIVA) campaign. We use ground based, ship, aircraft and balloon sonde observations made during the campaign, and a 3-D regional online transport and chemistry model capable of resolving clouds and convection explicitly that includes detailed bromine chemistry. The model simulates the temperature, wind speed, wind direction fairly well for the most part, and adequately captures the 10 convection location, timing, and intensity. The simulated transport of bromoform from the boundary layer up to 12 km compares well to aircraft observations to support our conclusions. The model makes several predictions regarding bromine transport from the boundary layer to the level of convective detrainment (11 to 12 km). First, the majority of bromine undergoes this transport as bromoform. Second, insoluble organic 15 bromine carbonyl species are transported to between 11 and 12 km, but only form a small proportion of the transported bromine. Third, soluble bromine species, which include bromine organic peroxides, hydrobromic acid (HBr), and hypobromous acid (HOBr), are washed out efficiently within the core of the convective column. Fourth, insoluble inorganic bromine species (principally Br2) are not washed out of the convective 20 column, but are also not transported to the altitude of detrainment in large quantities. We expect that Br2 will make a larger relative contribution to the total vertical transport of bromine atoms in scenarios with higher CHBr3 mixing ratios in the boundary layer, which have been observed in other regions. Finally, given the highly detailed description of the chemistry, transport and washout of bromine compounds within our 25 simulations, we make a series of recommendations about the physical and chemical processes that should be represented in 3-D chemical transport models (CTMs) and chemistry climate models (CCMs), which are the primary theoretical means of estimating the contribution made by CHBr3 and other very short-lived substances (VSLS) to the stratospheric bromine budget.